Self-terminating electrodeposition of Pt on WC electrocatalysts - Liu, Yihua (Chem Mater, 2020)
Self-terminated electrochemical deposition is used to grow Pt nanoparticles on tungsten monocarbide (WC) from a pH 4 electrolyte of 3 mmol/L K(2)PtCl(4)-0.5 mol/L NaCl. An unconventional potentiodynamic deposition program is used where nucleation is promoted at large overpotentials followed by growth termination at still larger overpotentials to yield a high coverage of Pt nanoparticles. Following three deposition cycles between −0.8 V(SCE) and −0.45 V(SCE), the surface is covered by a monolayer equivalent charge of Pt in the form of ≈3 × 10(11) particles/cm(2) that are ≈6.7 ± 1.1 nm in diameter. The number and size of nanoparticles increase monotonically for five deposition cycles. Area-normalized kinetics for hydrogen evolution (HER) and oxidation (HOR) on Pt-WC were determined in 0.5 mol/L H(2)SO(4). For the lowest surface coverage of Pt nanoparticles on WC, ≈ 0.01, an exchange current density of ≈ 100 mA/cm(2) is achieved, comparable to the highest reported values for Pt nanoparticles and ultramicroelectrodes. The area normalized apparent exchange current density decreases with increasing Pt coverage as the relative contribution of point versus planar diffusion decreases. Self-terminated electrodeposition of Pt provides an attractive approach to achieving ultra-low loadings of well-dispersed Pt nanoparticles on a non-precious metal support like WC.